Formulasi Sabun Cuci dari Minyak Jelantah dengan Penambahan Air Asam Sunti - Azmalina Adriani; Rinaldi Rinaldi; Hardiana Hardiana; Suci Suci; Irfan Mustafa (Oceana Biomedicina Journal, 2020)
Soap is a cleaning agent made from oil. Coconut oil that has been used is usually discarded as waste (minyak jelantah), with the additionof syringe acid water. Sunti acid water is one of the spices that contains quite high acidic compounds. The purpose of this study was to determine the characteristics of soaps containing Sunti acid water. This research is experimental to formulate laundry soap containing Sunti acid water, with used cooking oil. Soap formulation with Sunti acid waterconcentration 1.25% (F1), 1.50% (F2) and 1.75% (F3). The formula was evaluated with organoleptic parameters, moisture content, pH, homogeneity, high foam and clean power of soap. The results showed that soap (F1, F2, F3) was solid, brown in color and distinctively smelled of lemon, and the water content was 20.34%; 14.21% and 14.8%, pH ranges from 8-10, not homogeneous, foam height 48-78 cm and can be as a cleaner. So it can be concluded that Sunti acid water and used cooking oilcan be formulated in the form of soap and formula 3 is a good formula.